Spirituality as a Paradigm of Peace Education - Tobroni, Tobroni; Firmansyah, Eka; Rajindra, Rajindra; Fadli , Nazar (Multicultural Islamic Education Review, 2023)
This study aims to examine spirituality as a paradigm of peace education. This research presents solutions to various problems of Muslims in Indonesia today, especially the problem of the dry dimension of spirituality in their religion. The type of research used is library research. This research obtains information data by placing existing facilities in the library such as books, magazines, documents, records of historical stories or pure literature research related to the object of research. The results of this study explain that spirituality is the solution to achieving peace education. Spirituality is not a heresy in religion, but the spirit of religion itself. Religion is accompanied by an appreciation of spirituality that will get the essence of religion in the form of love for God and others. To approach the Khalik and also with his fellow beings, it is not enough just to go through the formalities. A spiritual approach full of values of love and compassion, ikhlas and ridlo will be more effective in arriving at justice and the Creator. On that basis, it is necessary to review the position and role of religion in human life.